2017
DOI: 10.4236/psych.2017.86060
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Object Complexity on Visual Working Memory Capacity

Abstract: The capacity of visual working memory (VWM) is regarded as one of the central themes in working memory. Related studies-on cognitive psychology and neuroscience level focused on the flexibility of capacity of working memory and the influencing factors. The current study aimed at the relationship of object complexity and VWM capacity, which used change detection paradigm in order to reveal the mechanism of object representation in visual working memory. We explored the impact of complexity on capacity of VWM by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Regarding storage active memory in individuals with major depression, it can be stated that this memory is reduced in both groups: individuals with major depression and normal individuals. Studies have shown that the test of storage active memory indicates less efficient performance in storage active memory in both groups of individuals with major depression and the control group (Chen et al, 2017;Cristofori et al, 2019). Thus, a disorder in storage active memory performance can be one of the cognitive characteristics of individuals with major depression.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding storage active memory in individuals with major depression, it can be stated that this memory is reduced in both groups: individuals with major depression and normal individuals. Studies have shown that the test of storage active memory indicates less efficient performance in storage active memory in both groups of individuals with major depression and the control group (Chen et al, 2017;Cristofori et al, 2019). Thus, a disorder in storage active memory performance can be one of the cognitive characteristics of individuals with major depression.…”
Section: Discussionmentioning
confidence: 99%
“…It is often associated with the prefrontal cortex of the brain and is crucial for decision-making and behavior regulation. In sum, working memory is a critical cognitive function that involves the temporary storage and manipulation of information which is influenced by various factors, ranging from genetic to environmental (1,4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The study of Chen (2021) explored DLL from various perspectives, including its cognitive impact. It implied that technology in language learning can influence cognitive functions, including working memory (4). Sweller (2020) provides instructional recommendations based on cognitive load W theory, relevant to technology's impact on reducing working memory load in educational settings (6).…”
Section: Introductionmentioning
confidence: 99%
“…Visual complexity is a well-known concept in many disciplines including neuroscience [1,2], cognitive psychology [3][4][5], product marketing [6,7], web design [8,9], art [10], etc. From a theoretical point of view, studying visual complexity has revealed information about the human visual system operation when evaluating stimuli [2], the memory formation mechanism [1], and its capacity [11]. It has also helped psychologists to understand how the visual complexity of scenes impacts emotion and attracts attention [12].…”
Section: Introductionmentioning
confidence: 99%